2018
DOI: 10.1186/s13024-018-0261-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling and biomarker identification reveal tissue specific effects of expanded ataxin-3 in a spinocerebellar ataxia type 3 mouse model

Abstract: BackgroundSpinocerebellar ataxia type 3 (SCA3) is a progressive neurodegenerative disorder caused by expansion of the polyglutamine repeat in the ataxin-3 protein. Expression of mutant ataxin-3 is known to result in transcriptional dysregulation, which can contribute to the cellular toxicity and neurodegeneration. Since the exact causative mechanisms underlying this process have not been fully elucidated, gene expression analyses in brains of transgenic SCA3 mouse models may provide useful insights.MethodsHere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 83 publications
10
46
0
Order By: Relevance
“…A high number of downregulated genes in both, the KI mice and humans were enriched for this cell type. These findings are in line with the transcriptomic studies of Ramani et al (2017) and Toonen et al (2018) in the YAC84Q mice, with oligodendrocytes appearing mainly affected by transcriptional changes. Ramani and colleagues further showed that ATXN3 is present in the cell nuclei of oligodendrocytes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A high number of downregulated genes in both, the KI mice and humans were enriched for this cell type. These findings are in line with the transcriptomic studies of Ramani et al (2017) and Toonen et al (2018) in the YAC84Q mice, with oligodendrocytes appearing mainly affected by transcriptional changes. Ramani and colleagues further showed that ATXN3 is present in the cell nuclei of oligodendrocytes.…”
Section: Discussionsupporting
confidence: 89%
“…While Shakkottai et al (2011) reported of changes in Purkinje cell firing concurring with behavioral deficits in YAC84Q mice even before observable neurodegeneration was detected, Costa Mdo et al (2013) described behavioral deficits in the same mouse model, but could not detect changes in Purkinje cell count. Toonen et al (2018) did not observe behavioral differences at the same time point. Therefore, the relation between Purkinje cell loss and a motor phenotype needs further investigation in several SCA3 models.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The comparison of both stages identified 54 genes with progressively changed expression during the disease course, including conspicuously strong downregulations for several enzymes of cholesterol biogenesis. It is crucial to note that also in a mouse model of SCA3 (Machado-Joseph disease), recent global transcriptome profiling demonstrated a significant enrichment of cholesterol biogenesis dysregulations in brainstem, but increased levels of ceramides, di- and triglycerides in blood [204]. Furthermore, for SCA3 it was shown that restoration of brain cholesterol homeostasis has therapeutic potential [131].…”
Section: Discussionmentioning
confidence: 99%